Self-templating noncatalyzed synthesis of monolithic boron nitride nanowires1. Issue 92 (8th October 2015) - Su, Chao-Hua; Wang, Ru-Zhi; Zhang, Yue-Fei; Zhang, Xing-Wang; Yan, Hui
<x xml:space="preserve">Abstract</x> Achieving economic orientation-controlled growth of monolithic nanowires remains a challenge.